2007
DOI: 10.1177/097133360701900204
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Influence of Emotional Intelligence on the Link Between Academic Self-efficacy and Achievement of University Students

Abstract: The study examined the moderating influence of emotional intelligence on the link between academic self-efficacy and achievement among university students. The participants in the study were 300 undergraduate students at the University of Ibadan, Ibadan, Nigeria. Their age ranged between 16.5 years and 30 years with mean age of 19.4 years. Two valid and reliable instruments were used to assess emotional intelligence and academic self-efficacy while participants’ first semester result was used as a measure of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
59
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(79 citation statements)
references
References 31 publications
14
59
1
5
Order By: Relevance
“…The finding is similar with past studied done by Li (2012), Tenaw (2013), Zajacova et al, (2005) and Adeyemo (2007) who found that academic self-efficacy was significantly correlated with student academic performance. And is in line with Bandura (1986) who stated that self-efficacy played a great role in determining how an individual feelings and thought motivated themselves, which then ultimately influenced their behavior and the outcome.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The finding is similar with past studied done by Li (2012), Tenaw (2013), Zajacova et al, (2005) and Adeyemo (2007) who found that academic self-efficacy was significantly correlated with student academic performance. And is in line with Bandura (1986) who stated that self-efficacy played a great role in determining how an individual feelings and thought motivated themselves, which then ultimately influenced their behavior and the outcome.…”
Section: Resultssupporting
confidence: 82%
“…The researcher reported that academic selfefficacy (β=0.355, p< .01) could significantly predict academic achievement better than attitude and effort in the study. Furthermore, Adeyemo (2007). Examined the moderating influence of emotional intelligence on the link between academic self-efficacy and achievement among undergraduate students of University of Ibadan, Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…El comportamiento de las personas, según Bandura (1997), puede ser mejor predicho por las creencias que los individuos tienen acerca de sus propias capacidades que por lo que en verdad pueden hacer, puesto que estas percepciones contribuyen a delinear qué es lo que las personas hacen con las habilidades y el conocimiento que poseen (Adeyemo, 2007;Blanco et al, 2011). Dicha autopercepción, denominada autoeficacia, ejerce una profunda influencia en la elección de tareas y actividades, en el esfuerzo y perseverancia de las personas cuando se enfrentan a determinados retos e incluso en las reacciones emocionales que experimentan ante situaciones difíciles (Vera et al, 2011).…”
Section: Introductionunclassified
“…Also, they perform better, they are more able to effectively self-regulate their learning and show greater intrinsic motivation when they learn (Cartagena, 2008;Salanova, Llorens, & Shaufeli, 2011). Consequently, improving self-efficacy expectations increases the motivation and performance in learning tasks (Adeyemo, 2007). Therefore, is not enough to be able to do something, people must be judged themselves capable or able to use the abilities and personal skills to a variety of circumstances, including emotional reactions to difficult situations (Blanco, Martínez, Zueck, & Gastélum, 2011).…”
Section: Introductionmentioning
confidence: 99%